Lost cat - Mader, C. Roger (Boston : Houghton Mifflin Books for Children, 2013)
Slipper the cat is mistakenly left behind in the commotion when the lady she has always lived with moves in with her daughter's family, so Slipper sets out to find someone new to adopt.
Keywords: Cats -- Juvenile fiction; Cat adoption -- Juvenile fiction; Pet adoption -- Juvenile fiction; Lost and found possessions -- Fiction; Cats -- Fiction; Cat adoption -- Fiction; Pet adoption -- Fiction; Cat adoption; Cats; Pet adoption; Fiction; Juvenile works